Mecanismos fisiológicos e moleculares de resposta de plantas de arroz(Oryza sativa L.) a altos níveis de infestação do ácaro fitófago Schizotetranychus oryzae (Acari: Tetranychidae) - Blasi, Édina Aparecida dos Reis (2018)
High levels of Schizotetranychus oryzae phytophagous mite infestation on rice leaves can severely affect pro- ductivity. Physiological characterization showed that S. oryzae promotes a decrease in chlorophyll concentration and the establishment of a senescence process in rice leaves. Late-infested leaves also present high levels of superoxide radical and hydrogen peroxide accumulation, along with high levels of membrane integrity loss, which is indicative of cell death. To better understand the rice molecular responses to high levels of mite in-festation, we employed the Multidimensional Protein Identification Technology (MudPIT) approach to identify differentially expressed proteins. We identified 83 and 88 proteins uniquely present in control and late-infested leaves, respectively, along with 11 and one proteins more abundant in control and late-infested leaves, re-spectively. S. oryzae infestation induces a decreased abundance of proteins related to translation, protease in-hibition, and photosynthesis. On the other hand, infestation caused increased abundance of proteins involved in protein modification and degradation. Our results also suggest that S. oryzae infestation interferes with in-tracellular transport, DNA structure maintenance, and amino acid and lipid metabolism in rice leaves. Proteomic data were positively correlated with enzymatic assays and RT-qPCR analysis. Our findings describe the protein expression patterns of late-infested rice leaves and suggest several targets which could be tested in future bio-technological approaches aiming to avoid the population increase of phytophagous mite in rice plants.